Two new classes of conjugate gradient method based on logistic mapping - Banaz Hamza Jahwar; Alaa Luqman ibrahim; Sherzad Muhammed Ajeel; Salah Gazi Shareef (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
Following the standard methods proposed by Polak-Ribiere-Polyak (P-R), in this work we introduce two new non-linear conjugate gradient methods for solving unconstraint optimization problem, our new methods based on P-R. Standard method (P-R) have performance well in numerical result but does not satisfy global convergency condition. In this paper we modified double attractive and powerful parameters that have better performance and good numerical result than P-R method, also each of our robust method can satisfies the descent condition and global convergency condition by using wolf condition. More over the second method modified by logistic mapping form, the main novelty is their numerical results and demonstrate performance well with compare to a standard method.